Andrew Lees, a visionary mentored by a madman - Cardoso, Francisco (Arquivos de Neuro-Psiquiatria, 2017)
Andrew Lees, Professor of Neurology at the National Hospital Queen Square (London, UK), has been recognized as the world’s most highly-cited researcher over the 200-year history of Parkinson’s Disease. Although he remains actively involved in the investigation of movement disorders, Prof. Lees embarked on a literary career that started in 2011 with the publication of a social history of his native Liverpool. His last work is Mentored by a Madman: The William Burroughs Experiment, which is reviewed here.
Keywords: Andrew Lees; William Burroughs; Gerald Stern; William Gooddy; Marcel Proust